A Survey of Musculoskeletal Disorders in the Orthopaedic Surgeon: Identifying Injuries, Exacerbating Workplace Factors, and Treatment Patterns in the Orthopaedic Community. (24th May 2022) - Swank, Katherine R.; Furness, Jamie E.; Baker, Erin; Gehrke, Corinn K.; Rohde, Rachel
Abstract : Introduction: As demand for orthopaedic care increases, the orthopaedic community must preserve access to skilled physicians. Workplace hazards and related injuries or conditions contribute to musculoskeletal (MSK) stress on orthopaedic surgeons, which can lead to undesirable medical leaves of absence or early retirement. The purpose of this study was to identify and characterize work-related and non–work-related MSK conditions that affect orthopaedic surgeons and differential injury patterns among male and female surgeons. This study hypothesized that MSK conditions would be exacerbated by work, correlate with age, and show gender-based disparities. Identifying MSK conditions and associated workplace hazards may ultimately help guide preventive or protective efforts. Methods: Following IRB and society approvals, a modified 15-question physical discomfort survey was emailed to a randomized selection of American Academy of Orthopaedic Surgeons (AAOS) members and all Ruth Jackson Orthopaedic Society members. Data were deidentified and merged by AAOS; analyses were performed by the authors. Results: Most surgeons reported at least one MSK condition (86%; 95% male versus 82% female, P = 0.317), with an average of two conditions per surgeon. Low back pain (56%) and neck pain (42%) were the two most common conditions reported. Male surgeons were more likely to report medial epicondylitis ( P = 0.040), lateral epicondylitis ( P ≤ 0.001), low back pain ( P = 0.001), and lumbar radiculopathy ( P = 0.001); however, male respondents were significantly older than female respondents (57 versus 43 years, P ≤ 0.0001), and some conditions were age-correlated. Most respondents reported at least one work-attributed MSK condition (64%; 68% male versus 62% female, P = 0.806). Caseload was not associated with an increased number of work-related MSK conditions; yet, 60% of surgeons reported that work worsened symptoms. Surgical treatment was sought most often for lumbar radiculopathy (6%) and carpal tunnel syndrome (6%). Sixty-nine leaves of absence were reported; most less than 1 month (55%). Exacerbating workplace factors included positioning (patient/surgeon), instruments, and personal protective equipment. Discussion: Work-related MSK conditions are common among orthopaedic surgeons. Greater awareness of potential workplace-related hazards and conditions is needed to address and mitigate negative MSK health effects on orthopaedic surgeons.